(untitled) (Purbanchal University Health Journal, 2025)
Introduction: In the occurrence of disaster, awareness on disaster preparedness is the equipment of healthcare professionals, which they can use to manage the disaster. Objective: This study aims to assess the knowledge of disaster preparedness and find out the association between disaster preparedness with socio-demographic factors among Rapid Response Teams (RRT) of teaching district hospitals linked to BPKIHS, Koshi Province, Nepal. Method: A descriptive cross sectional study was conducted among RRT of all teaching district hospitals of BPKIHS in Koshi Province, Nepal. Data was collected by total enumerative sampling survey after obtaining ethical clearance from IRC BPKIHS (Ref. No.151/076/077 Code No: 1561/019) with 80 samples. The data was collected in four weeks through a modified structured questionnaire based on Global Assessment of National Health Sector Emergency Preparedness and Response developed by WHO. Mann- Whitney and Kruskal Wallis H Test was used to find out association. Result: Total knowledge score on disaster preparedness among RRT members was 65.86±23.24. One-fourth of RRT (25%) had poor knowledge on disaster preparedness. There was significant association of knowledge score on disaster preparedness with working district and organization of RRT members, emergency preparedness & response background of RRT. Conclusion: This study concludes that only minimum (15%) of respondents had good knowledge on disaster preparedness.